Delineating the interactions between the cannabinoid CB2 receptor and its regulatory effectors; β‐arrestins and GPCR kinases. (7th February 2022) - Patel, Monica; Matti, Christoph; Grimsey, Natasha L.; Legler, Daniel F.; Javitch, Jonathan A.; Finlay, David B.; Glass, Michelle
Abstract : Background and Purpose: The cannabinoid CB2 receptor (CB2 ) is a promising therapeutic target for modulating inflammation. However, little is known surrounding the mechanisms underpinning CB2 desensitisation and regulation, particularly the role of GPCR kinases (GRKs). Here, we evaluated the role of six GRK isoforms in β‐arrestin recruitment to CB2 . Mutagenesis of several distal C‐terminal aspartic acid residues was also performed in an attempt to delineate additional structural elements involved in the regulation of CB2 . Experimental Approach: In CB2 ‐expressing HEK 293 cells, β‐arrestin translocation was measured using real‐time BRET assays. G protein dissociation BRET assays were performed to assess the activation and desensitisation of CB2 in the presence of β‐arrestin 2. Key Results: Overexpression of GRK isoforms 1–6 failed to considerably improve translocation of either β‐arrestin 1 or β‐arrestin 2 to CB2 . Consistent with this, inhibition of endogenous GRK2/3 did not substantially reduce β‐arrestin 2 translocation. Mutagenesis of C‐terminal aspartic acid residues resulted in attenuation of β‐arrestin 2 translocation, which translated to a reduction in desensitisation of G protein activation. Conclusion and Implications: Our findings suggest that CB2 does not adhere to the classical GPCR regulatory paradigm, entailing GRK‐mediated and β‐arrestin‐mediated desensitisation. Instead, C‐terminal aspartic acid residues may act as phospho‐mimics to induce β‐arrestin activation. This study provides novel insights into the regulatory mechanisms of CB2, which may aid in our understanding of drug tolerance and dependence.